IMPROVEMENT OF THE VEGETABLE OIL PRODUCTION TECHNOLOGY BY DEODORIZATION PROCESS USING FLOATING PACKING - Hakimova Nodira Hayrullayevna; Umarov Dilshod Ilhom ugli (Web of Journals Publishing, 2025)
This article explores the process of deodorization of vegetable oils and methods for its improvement. In particular, the deodorization process using floating packing is examined. The effectiveness of this method, its energy efficiency, and its impact on quality indicators are analyzed.
Keywords: Vegetable oil, deodorization, floating packing, technology, quality, energy efficiency.